(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tooth wear is a multifactorial and variable aspect of dental problems. Successful management of tooth wear is a very important and upcoming topic of the dental field. Full mouth rehabilitation requires a combined orthodontic, prosthodontic and endodontic approach for successful treatment outcome. To evaluate the various types of adjunct therapies performed in patients undergoing tooth supported Full Mouth Rehabilitation treatment (FMR).This study was designed as a retrospective study. A total of 65 patient records who underwent tooth supported full mouth rehabilitation treatment were acquired by analysing records of 86000 patient data treated from June 2019- March 2020. Descriptive statistics were used to analyse the frequency and percentage of different types of adjunct therapies performed. Chi square test was used to find correlation between age and gender with the type of adjunct therapy performed. SPSS version 20 software was used to perform statistics. 30.8% of the cases undergoing tooth supported FMR treatment underwent RCT/ endodontic treatment. 10.8% of the cases underwent Periodontal therapy. 12.3% of the cases required both endodontic and periodontal therapy. 46. 2% of the cases did not require any adjunct therapy. Age and gender did not have any significant correlation with the type of adjunct therapy that was performed. Their P values were 0.471 and 0.887 respectively. Within the limitations of the study, it can be concluded that among the adjunct therapies performed in tooth supported FMR cases, endodontic treatment was found to be the most frequently carried out. There was no positive correlation between age and gender with the type of adjunct therapy used.